Proceedings of the 2010 American Control Conference 2010
DOI: 10.1109/acc.2010.5530571
|View full text |Cite
|
Sign up to set email alerts
|

Choice modeling of relook tasks for UAV search missions

Abstract: Abstract-This paper addresses human decision-making in supervisory control of a team of unmanned vehicles performing search missions. Previous work has proposed the use of a twoalternative choice framework, in which operators declare the presence or absence of a target in an image. It has been suggested that relooking at a target at some later time can help operators improve the accuracy of their decisions but it is not well understood how -or how well -operators handle this relook task with multiple UAVs. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 14 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…In this paper, it was assumed that all the tasks which the support system selected, will be serviced by the operator. Another possibility is to give operators ability to requeue tasks which has been shown to improve overall performance [2]. Developing stable attention allocation schemes with requeuing poses additional challenges and needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, it was assumed that all the tasks which the support system selected, will be serviced by the operator. Another possibility is to give operators ability to requeue tasks which has been shown to improve overall performance [2]. Developing stable attention allocation schemes with requeuing poses additional challenges and needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the optimal task release rate is also determined. Bertuccelli et al [2] study the queues with re-look tasks. They consider a queue in which the arriving difficult tasks are placed in an orbit queue for later viewing while simple tasks are immediately processed.…”
Section: Introductionmentioning
confidence: 99%
“…A similar model has also been reported in the human factors literature, e.g., see [9]. Recently, there has also been interest in incorporating error rates into the performance metric for humans in a queueing setup, e.g., see [10], [11].…”
Section: Introductionmentioning
confidence: 87%
“…b Preliminary investigation in the role of preemption has been addressed in a previous paper investigating use of relooks to improve the likelihood of detection [19]. Use of preemption for this work is investigated in an ongoing human-in-the-loop experiment.…”
Section: Iia Scheduling Formulationmentioning
confidence: 99%
“…Previous work has shown that search times can be modeled with a corresponding lognormal distribution [19]. A more detailed discussion on the sensitivity of the scheduling algorithms to the knowledge of search times in the next sections, but one method for handling the uncertainty in the start (respectively, search) times is to substitute the expected values,s j (respectively, t j ), and find the optimal schedule as follows: …”
Section: Iib Sensitivity To Uncertainty In Search Timesmentioning
confidence: 99%